2022
DOI: 10.1371/journal.pone.0274454
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-care behavior in patients with pre-dialysis or dialysis-dependent chronic kidney disease

Abstract: Self-care behavior plays a pivotal role in the management of chronic kidney disease. Improved self-care behavior in patients with chronic kidney disease is a key factor in health management and treatment adherence. This study aimed to evaluate the participants’ general and medical condition-related characteristics, physiological indices and the level of health literacy affecting self-care behavior in patients with chronic kidney disease in South Korea. The data of 278 participants were analyzed using t-test, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Patients on HD typically visit the hospital for dialysis sessions and will engage in consultations with nurses, addressing issues related to self-care behaviors, including dietary restrictions, exercise, medication adherence, and the management of comorbidities and complications. This heightened support from healthcare providers is especially beneficial for individuals with dialysis-dependent CKD, contributing to positive changes in their self-care behaviors [ 25 ]. Living with CKD presents challenges for both patients and their care partners.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on HD typically visit the hospital for dialysis sessions and will engage in consultations with nurses, addressing issues related to self-care behaviors, including dietary restrictions, exercise, medication adherence, and the management of comorbidities and complications. This heightened support from healthcare providers is especially beneficial for individuals with dialysis-dependent CKD, contributing to positive changes in their self-care behaviors [ 25 ]. Living with CKD presents challenges for both patients and their care partners.…”
Section: Discussionmentioning
confidence: 99%
“…Patients possessing stronger physical, cognitive and psychological capacities are more likely to adopt a proactive approach to their medical responsibilities, seeking adequate knowledge and available resources to enhance their autonomy 73 . Additional support at the social and organizational levels might further strengthen patients' abilities to engage 74–76 …”
Section: Discussionmentioning
confidence: 99%
“…73 Additional support at the social and organizational levels might further strengthen patients' abilities to engage. [74][75][76] Twenty-four articles were identified and included in this review.…”
Section: Proposed Modelmentioning
confidence: 99%
“…In CKD, it can be challenging to follow treatment tasks because of the sheer number and, at times, its complexity (e.g., other comorbid conditions, kidney replacement therapy [KRT]). For instance, the reported prevalence of medication nonadherence in those not receiving KRT is about 40% (Tesfaye et al, 2021), while other studies have reported low levels of adherence with dietary changes, smoking behaviours and BP monitoring (Ahn et al, 2022; Wang et al, 2019). In two systematic reviews of studies involving people receiving haemodialysis (HD), nonadherence to diet and fluid restrictions was between 47% and 72% (Vijay & Kang, 2021), and for medications between 12% and 98% (Ghimire et al, 2015).…”
Section: Introductionmentioning
confidence: 99%